A bioenergetic framework for aboveground terrestrial food webs. (March 2023) - Valdovinos, Fernanda S.; Hale, Kayla R.S.; Dritz, Sabine; Glaum, Paul R.; McCann, Kevin S.; Simon, Sophia M.; Thébault, Elisa; Wetzel, William C.; Wootton, Kate L.; Yeakel, Justin D.
Abstract: Bioenergetic approaches have been greatly influential for understanding community functioning and stability and predicting effects of environmental changes on biodiversity. These approaches use allometric relationships to establish species' trophic interactions and consumption rates and have been successfully applied to aquatic ecosystems. Terrestrial ecosystems, where body mass is less predictive of plant–consumer interactions, present inherent challenges that these models have yet to meet. Here, we discuss the processes governing terrestrial plant–consumer interactions and develop a bioenergetic framework integrating those processes. Our framework integrates bioenergetics specific to terrestrial plants and their consumers within a food web approach while also considering mutualistic interactions. Such a framework is poised to advance our understanding of terrestrial food webs and to predict their responses to environmental changes. Highlights: Bioenergetic food web approaches have fueled a major body of ecological research, but their use of body size for inferring trophic interactions and consumption rates is not sufficient for terrestrial systems. Terrestrial plants exhibit large variation in tissue growth and turnover not included in bioenergetic models, and their biotic interactions are driven by defenses, different chemical composition of their tissues, and herbivory on different tissues. Plant growth rate represents a key axis of variation for plant biotic interactions, from fast with low investment in storage and defense to slow with high investment in storage and defense. Incorporating the continuum of plant growth strategies can serve as a fulcrum for a new bioenergetic food web approach that predicts the network structure and stability of terrestrial food webs and their biodiversity–ecosystem functioning relationships.